1999
DOI: 10.1038/sj.ijo.0801045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sibutramine on resting energy expenditure and adrenaline-induced thermogenesis in obese females

Abstract: BACKGROUND: Sibutramine, an inhibitor of serotonin and noradrenaline uptake, reduces appetite to cause weight loss. This study tested the hypothesis that an increase in energy expenditure also contributes to this weight loss. In addition, the effects of sibutramine on adrenaline induced changes in heart rate and cardiac output were determined METHODS: Nineteen obese females randomly received either sibutramine 15 mg daily or placebo for 12 weeks along with dietary advice. Resting energy expenditure (REE) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 14 publications
0
64
1
6
Order By: Relevance
“…8,14 Additionally, sibutramine has been shown to increase energy utilisation. 19,20 The increased energy utilisation activity of sibutramine may be indirectly generated by central stimulation of efferent sympathetic output to the ␤ 3 -adrenoceptors in brown adipose tissue. 20,21 Increase in energy expenditure with sibutramine treatment has been reported in two studies 19,20 Journal of Human Hypertension although not in one other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,14 Additionally, sibutramine has been shown to increase energy utilisation. 19,20 The increased energy utilisation activity of sibutramine may be indirectly generated by central stimulation of efferent sympathetic output to the ␤ 3 -adrenoceptors in brown adipose tissue. 20,21 Increase in energy expenditure with sibutramine treatment has been reported in two studies 19,20 Journal of Human Hypertension although not in one other.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The increased energy utilisation activity of sibutramine may be indirectly generated by central stimulation of efferent sympathetic output to the ␤ 3 -adrenoceptors in brown adipose tissue. 20,21 Increase in energy expenditure with sibutramine treatment has been reported in two studies 19,20 Journal of Human Hypertension although not in one other. 22 This possible dual mechanism of action may enhance the efficacy of sibutramine by diminishing the decrease in metabolic rate normally encountered upon initial weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Sibutramine mediates increased satiety, although a mild increase in energy expenditure may also contribute to weight loss. 8 Norepinephrine uptake inhibition with sibutramine in peripheral tissues could exacerbate arterial hypertension through an increase in synaptic norepinephrine concentrations. Indeed, when applied locally to peripheral tissues, norepinephrine transporter blockade increases norepinephrine overflow.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Controlled clinical studies have shown that sibutramine produces dose-related weight reduction in obese subjects, as early as 2 weeks after initiation of treatment. 13 However, the norepinephrine activation induced by sibutramine administration could lead to an increase in arterial blood pressure and elevation of heart rate in some patients.…”
Section: Introductionmentioning
confidence: 99%